2022
DOI: 10.1039/d1nr07987e
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid-polypyrrole multifunctional coating layer enhancing the interface effect and efficient Li-ion transport of a phosphorus anode

Abstract: Phosphorus has been considered as a promising anode for lithium-ion batteries because of its high specific capacity of 2596 mA h g−1 and safe lithiation voltage of 0.7 V. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…Figure S10 displays the galvanostatic charge and discharge profiles of the PANI/(BP–CNT) composite at current densities of 0.1–0.5 A g –1 . Compared with the reported BP composite studies, as shown in Table , our result exhibits better cycle stability than the reported results, ,, possessing a reversible capacity of 1150.7 mA h g –1 after cycling 100 at a current density of 0.1 A g –1 .…”
Section: Resultscontrasting
confidence: 49%
“…Figure S10 displays the galvanostatic charge and discharge profiles of the PANI/(BP–CNT) composite at current densities of 0.1–0.5 A g –1 . Compared with the reported BP composite studies, as shown in Table , our result exhibits better cycle stability than the reported results, ,, possessing a reversible capacity of 1150.7 mA h g –1 after cycling 100 at a current density of 0.1 A g –1 .…”
Section: Resultscontrasting
confidence: 49%
“…[52,54] Mixing the P with carbons having the high conductivity is a facile strategy to develop the storage capacity of P. For instance, Li et al, used the tannin acid (TA) and pyrrole (Py) to construct the multi-layer carbons on the surface of P based carbon nanotube (P-CNT) by an in situ polymerization method. [55] A lot of oxygen atoms in TA possess the strong adsorptive ability for P and its compounds (Li x P s ), leading to TA could be coated on the surface of P very well. The carbons obtained by carbonizations of Py exhibit the tremendous conductivity.…”
Section: Enhancing the Storage Capacity Of Materials Belonging To The...mentioning
confidence: 99%
“…Among the potential anode materials, phosphorus (P) has been regarded as a promising anode with several advantageous features, 7,8 including the high theoretical specific capacity (2596 mAh g −1 ) and the relatively low but safe working potential of ∼0.7 V vs Li + /Li for fast charging (Figure S1) in the Supporting Information. 9−14 However, its practical applications are still hampered by its large volume variations, various sides reactions between the electrode and electrolytes resulting from the unstable solid electrolyte interphase (SEI), the shuttle effect of soluble polyphosphides upon lithiation/ delithiation cycles, and sluggish reaction kinetic of the multiphase transformation from solid P to soluble polyphosphides and to solid Li 3 P. 15 In order to address the aforementioned issues, several approaches based on surface coating/modification have been reported, using conductive polymers (such as polypyrrole, 16 tannic acid−polypyrrole, 17 and polydopamine 18 ) and inactive inorganic materials (such as LiF 19 and phosphorus oxide 20 ). While the conductive polymers can serve as flexible substrates to buffer the volume expansion of P particles, the active P utilization was not significantly improved, due to the low polyphosphides adsorption capability and the weak reactivation of the phosphorus species trapped on the conductive polymers.…”
mentioning
confidence: 99%
“…In order to address the aforementioned issues, several approaches based on surface coating/modification have been reported, using conductive polymers (such as polypyrrole, tannic acid–polypyrrole, and polydopamine) and inactive inorganic materials (such as LiF and phosphorus oxide). While the conductive polymers can serve as flexible substrates to buffer the volume expansion of P particles, the active P utilization was not significantly improved, due to the low polyphosphides adsorption capability and the weak reactivation of the phosphorus species trapped on the conductive polymers.…”
mentioning
confidence: 99%